An Approach for Modeling, Simulation, and Optimization of Catalytic Production of Methyl Ethyl Ketone - Zahra Parhizi; Milad Nayebi; Edris Mohammadzadeh; Reza Torfi (Journal of Chemistry)
The current exploration manifests the progress of a one-dimensional reactor for the production of methyl ethyl ketone (MEK) as a commercial-industrial solvent with a relatively rapid evaporation rate and high solvation ability. MEK has been extensively utilized in colorings, printing, artificial leather, and base oils. One of the methods for the production of MEK is catalytic dehydrogenation of 2-butyl alcohol in the temperature range of 650–750 K utilizing spherical ZnO catalyst. Considering the high cost of fossil fuels to achieve optimal energy consumption, thermal coupling with the Fischer–Tropsch reaction was employed. Eventually, an evolutionary genetic algorithm was adopted to optimize the reactor to maximize MEK production. MATLAB software was utilized for the modeling and optimization. The modeling results were verified by industrial data. Moreover, they indicated a 37 and 55.4% increase in the production rate of thermal coupling and optimal thermal coupling reactors, respectively.